Measuring autonomy: evidence from Bangladesh - Vaz, A; Alkire, S; Quisumbing, A; Sraboni, E (Oxford Poverty and Human Development Initiative, 2019)
The search for rigorous, transparent, and domain-specific measures of empowerment that can be used for gendered analysis is ongoing. This paper explores the value-added of a new measure of domain-specific autonomy. This direct measure of motivational autonomy emanates from the ‘self-determination theory’ (Ryan and Deci, 2000). We examine in detail the Relative Autonomy Index (RAI) for individuals, using data representative of Bangladeshi rural areas. Based on descriptive statistical analyses, we conclude that the measure and its scale perform broadly well in terms of conceptual validity and reliability. Based on an exploratory analysis of the determinants of autonomy of men and women in Bangladesh, we find that neither age, education, nor income are suitable proxies for autonomy. This implies that the RAI adds new information about the individuals and is a promising avenue for further empirical exploration as a quantitative yet nuanced measure of domain-specific empowerment.